If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + 18 + -15z + 107 = 8 + -9 Reorder the terms: 18 + 107 + 6z + -15z = 8 + -9 Combine like terms: 18 + 107 = 125 125 + 6z + -15z = 8 + -9 Combine like terms: 6z + -15z = -9z 125 + -9z = 8 + -9 Combine like terms: 8 + -9 = -1 125 + -9z = -1 Solving 125 + -9z = -1 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-125' to each side of the equation. 125 + -125 + -9z = -1 + -125 Combine like terms: 125 + -125 = 0 0 + -9z = -1 + -125 -9z = -1 + -125 Combine like terms: -1 + -125 = -126 -9z = -126 Divide each side by '-9'. z = 14 Simplifying z = 14
| (s^2+s+1)=0 | | 4v-7=5t*7v | | (s^3+2*s^2+2*s+1)=0 | | 3(4x-2)=4(3x-1)+x | | 3x^9+3x-27= | | 3(4x-2)=4(3x-1)+1 | | 4x^5-28x^3= | | c=10+(-15)+(-8)+7 | | 15v-60=-3(20-5v) | | 8a-2=22 | | 11x+4+5=20+2x+20x | | x^3+4x^2= | | 6p-15p=81 | | 7x+4y-3x+10z+5y= | | 3xy-3=-5y | | w=9250-60(50t) | | x+2(2x+5)=4(x+3) | | 7-44= | | 3(x-4)=4(x+5) | | 29-(-23)= | | 2(2r-4)=-52 | | -6n-20=-14n+4 | | 3t+9-2t-2=0 | | x/8-7=-9 | | 50+(-50)= | | -31=2+2a | | (3x-4y)(3x+4y)=2 | | -9+(-3)+12+(-3)=f | | 7(2n-4)=(5n+6)+1 | | 7g-6=-20 | | x+5(18-x)=46 | | 28s^2-8s= |